THE TRIO ATTRIBUTE AS A FUNCTIONAL FEATURE IN VARIOUS TEXT MINING COMPUTATIONAL APPROACHES - Dr. Tareef Kamil Mustafa (International Journal of Advanced Science and Technology, 2020)
This research is concerned in using the trio attribute as the main feature instead of the regular widely used “single word” or even “pair of words” in the latest computational approaches projects. The authorship detection subject has been chosen to prove the efficiency and the consistency of the trio as the most functional feature among others.